Carbon-negative co-production of methanol and activated carbon from bagasse pyrolysis, physical activation, chemical looping, and methanol synthesis - Su G.; Zulkifli N.W.M.; Liu L.; Ong H.C.; Ibrahim S.; Yu K.L.; Wei Y.; Bin F. (Elsevier Ltd, 2024)
Methanol is regarded as an important chemical precursor in the chemical industry and has huge potential to replace gasoline and diesel as vehicle fuel. Biomass to methanol is a sustainable and green production method, but its economic and environmental viability is contingent on production technologies and geographic context. This study proposed a carbon-negative methanol production method that integrated four modules of bagasse pyrolysis, physical activation, chemical looping, and methanol synthesis in the context of China. Three scenarios, including co-production of methanol and biochar, co-production of methanol and activated carbon, and co-production of methanol and activated carbon with extra hydrogen, were put forward and simulated in Aspen Plus. An evaluation system was established to quantitatively assess the carbon and energy efficiencies and economic and environmental benefits of the three scenarios. The results suggested that the addition of hydrogen effectively increased the methanol yield in Scenario 3, leading to high carbon and energy efficiencies. Scenarios 1 and 2 exhibited better economic and environmental performance with low payback periods of 6.53 and 5.80 years and low global warming potentials of ?1631.18 and ?710.28 kg CO2-eq/t methanol. However, Scenario 3 would be economically and environmentally feasible by decreasing hydrogen production costs and implementing green hydrogen production methods in the foreseeable future. This study provides a viable approach for sustainable methanol production in China, thereby aligning with the current imperative of achieving carbon neutrality. 2023